Maqāṣid al-Sharī‘ah Insights on HDI and Islamic Economic Policy - Arya, Prima Ariyo Widodo; Risdayani, Risdayani; Hidayat, Wahyu`; Ali Tjenra, Ahmad Raden (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyse the influence of average years of schooling and life expectancy on Indonesia's Human Development Index (HDI) for the period 2021-2023 and its implications from an Islamic economic perspective based on maqāṣid al-Syarī'ah. This study employs a mixed-method approach, combining quantitative analysis through multiple linear regression tests to analyse the impact of average years of schooling and life expectancy on Indonesia's HDI for the 2021-2023 period, with qualitative analysis through content analysis from the perspective of maqāṣid al-Syarī‘ah. The results of this study indicate that average years of schooling and life expectancy have a positive and significant impact on the improvement of the Human Development Index (HDI) in Indonesia for the period 2021-2023, contributing 73.50 per cent to HDI variation. The increase in average years of schooling reflects improved access to education, thereby supporting workforce quality, while the stability of life expectancy indicates the success of healthcare services and improving living conditions for the population. From an Islamic economic perspective, these findings reinforce the connection between HDI indicators and the five objectives of maqāṣid al-Syarī‘ah, namely the protection of religion, life, intellect, lineage, and property, indicating that HDI improvement supports human development aligned with Sharia values. The implications of these findings underscore the importance of integrating education and health policies with environmental conservation policies to achieve a fair, sustainable, and prosperous Islamic economy for society.